Social disorientation of budget support for investment projects - V. V. Maximov (Модернизация, инновация, развитие)
Purpose: of the study is to identify factors that hinder budget support for investment projects aimed at combating poverty due to the deprivation of economically accessible social infrastructure (deprivation poverty).Methods: the work used traditional methods of scientific analysis, as well as an interdisciplinary approach characteristic of the study of social well-being problems in the context of the availability of social benefits created by social infrastructure facilities. The research is based on the application of social goal-setting documents, methodological documents regulating investment activities and budget support, Rosstat data, EIS «Procurement», EMISS, GIS «Electronic Budget».Results: the identification of factors of social well-being was carried out and the justification of the level of deprivation poverty in relation to the available social infrastructure was carried out. The necessity of independent regulation of the market of the poor suffering from such deprivations is confirmed. Based on the analysis of methodological tools for assessing the feasibility of budgetary support for investment projects in social infrastructure, methodological problems have been identified and the inapplicability of the existing approach for the market under study have been proved. Proposals are formulated to change approaches to calculating the budgetary efficiency of investment projects aimed at the infrastructural development of social industries.Conclusions and Relevance: a growing number of the deprived poor are suffering from a lack of supply of economically accessible social infrastructure and services. The study shows that the involvement of private investment in the creation of such facilities, taking into account the need for non-market pricing, will require changes in the methodological approach of the state to budget support for investment projects. It is necessary to abandon the percentage and return principles and replace them with compensatory ones for servicing vulnerable categories. The social development of the country should be based on the social well-being of all segments of the population, without extreme gaps among them. For sustainable development, flexible methodological tools are needed, based on the dependence of the amount of budget support on the number of social effects generated by the project.